2013
DOI: 10.1002/jnr.23203
|View full text |Cite
|
Sign up to set email alerts
|

Preischemic exercise reduces brain damage by ameliorating metabolic disorder in ischemia/reperfusion injury

Abstract: Physical exercise preconditioning is known to ameliorate stroke-induced injury. In addition to several other mechanisms, the beneficial effect of preischemic exercise following stroke is due to an upregulated capacity to maintain energy supplies. Adult male Sprague-Dawley rats were used in exercise and control groups. After 1-3 weeks of exercise, several enzymes were analyzed as a gauge of the direct effect of physical exercise on cerebral metabolism. As a measure of metabolic capacity, an ADP/ATP ratio was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Previous studies have demonstrated that EP can improve BBB function, reduce the severity of ischemic brain injury, 30,31 improve cerebral blood flow, regulate the expression of endothelin-1, and improve neurological deficits 32 after cerebral ischemia by regulating imbalances in MMP-9 and TIMP-1 expression. EP is also reported to interact with superoxide dismutase, reduce malondialdehyde accumulation, and enhance cellular antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that EP can improve BBB function, reduce the severity of ischemic brain injury, 30,31 improve cerebral blood flow, regulate the expression of endothelin-1, and improve neurological deficits 32 after cerebral ischemia by regulating imbalances in MMP-9 and TIMP-1 expression. EP is also reported to interact with superoxide dismutase, reduce malondialdehyde accumulation, and enhance cellular antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, clinical studies in stroke patients conducted in the early 1970s first reported that the energy requirements of patients with hemiparetic gait were elevated by 55%–100% compared to normal controls (Corcoran et al, 1970; Gersten and Orr, 1971). In animal studies, hypoxic stress and forced post-stroke physical exercise result in an increased demand for ATP-generating capacity and elevated glucose metabolism in the brain (Kinni et al, 2011; Dornbos et al, 2013). Together, these results indicate that exercise increases the metabolic activity of the brain, driving it to consume more energy via glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Postinjury exercise therapy that aims to ameliorate physical disability after stroke has long been considered a logical candidate for neuroprotective rehabilitation (Arya et al, 2011). In previous studies, neuroprotection has been consistently evidenced by physical exercise through reduced sequelae of brain infarction with improved functional outcomes in a rat ischemic stroke model (Ding et al, 2006;Dornbos et al, 2013;Q.W. Zhang et al, 2013).…”
mentioning
confidence: 99%